2020
DOI: 10.1007/s11214-020-0639-1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the in Situ Probe Designs from Recent Ice Giant Mission Concept Studies

Abstract: For the Ice Giants, atmospheric entry probes provide critical measurements not attainable via remote observations. Including the 2013-2022 NASA Planetary Decadal Survey, there have been at least five comprehensive atmospheric probe engineering design studies performed in recent years by NASA and ESA. International science definition teams have assessed the science requirements, and each recommended similar measurements and payloads to meet science goals with current instrument technology. The probe system conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…Modern explorations of possible mission scenarios to the ice giants Uranus and Neptune [1] [2][3][4] have motivated a revision of what we know about these planets and their planetary systems. Recent reviews explore their atmospheric dynamics [5], mean circulation patterns [6] and vertical structure [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Modern explorations of possible mission scenarios to the ice giants Uranus and Neptune [1] [2][3][4] have motivated a revision of what we know about these planets and their planetary systems. Recent reviews explore their atmospheric dynamics [5], mean circulation patterns [6] and vertical structure [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…This enthusiasm for Ice Giants from both sides of the Atlantic led to a joint study , which looked closely at a number of potential mission architectures [10]. Since then, ESA has considered a palette of potential contributions to a US-led mission 3 (2018-19), including secondary orbiters and atmospheric probes, as reviewed by Simon et al [11] and advocated by Mousis et al ([12], this issue). At the time of our submission to Voyage 2050, it had been hoped that such a contribution, at the ∼e0.5bn level, might be included in a proposed increase in ESA's science budget in 2019.…”
Section: Ice Giants In Esa's Cosmic Visionmentioning
confidence: 99%
“…High inclinations are easier to achieve at Uranus, although Triton can be used to drive a satellite tour at Neptune. The delivery and telemetry for an atmospheric entry probe must also be considered in an orbital tour design (e.g., Simon et al, 2020). We also propose that distinct phases of an orbital tour be considered, balancing moderate orbital distances (for remote sensing, outer magnetosphere science, and a satellite tour) with close-in final orbits (for gravity science and inner magnetosphere),…”
Section: Payload Considerationsmentioning
confidence: 99%
“…An ambitious mission to an Ice Giant System would largely build on existing mature technologies (e.g., see the discussion of payload development in Section 4.1), but several challenges have been identified that, if overcome, would optimise and enhance our first dedicated orbital mission to these worlds. Note that we omit the need for ablative materials on atmospheric entry probes, which will be required for in situ science (Mousis et al, 2018, Simon et al, 2020. Key areas where technology maturations are required include:…”
Section: Mature and Developing Technologiesmentioning
confidence: 99%